Improving recovery and stability of touch DNA. (December 2017) - Aloraer, D.; Hassan, N.H.; Albarzinji, B.; Goodwin, W.
Abstract: Touch samples by their nature do not contain large amounts of biological material, especially compared to biological fluids such as blood, semen or saliva. Consequently, more careful recovery and storage are desirable in order to maximise the amount of DNA available. The main aim of the work presented is to determine whether detergent-based wetting agents increased DNA yield from touch samples when compared to water as a wetting agent. The results show that the use of the detergent-based lysis buffer led to greater DNA recovery from the fingerprints than when distilled water was used. The use of the lysis buffer in the touch DNA sample collection improved DNA recovery and stability over 24 h post-collection.